PEMBERDAYAAN MASYARAKAT ADAT TERPENCIL MELALUI MODEL PENDIDIKAN LUAR SEKOLAH - Puji Hadiyanti (Direktorat Pembinaan Guru dan Tenaga Kependidikan Pendidikan Anak Usia Dini Kementerian Pendidikan dan Kebudayaan bekerjasama dengan Fakultas Ilmu Pendidikan Universitas Negeri Jakarta, 2009)
Empowering the community of remote custom is an effort to raise dignity and prestige of human to the real position. There are many challenges that must be faced especially in empowering potential that exists in human itself. Modeling out of school education tries to position itself as one of approaches that can be used in the effort of empowering the community of remote custom. Developing theori awareness in the importance of study process as an effort of behavior changes, then it will open their access toward an appropriate study process to their way of life and their requirement in order to increase their power, their cognitive, their psychology, their economic and their politic that is a form of done empowering. Although it cannot happen in short time, out of school education is believed will make them more adjustable toward environment changes.